Axonal transcription factors: Novel regulators of growth cone‐to‐nucleus signaling. Issue 3 (30th September 2013) - Ji, Sheng‐Jian; Jaffrey, Samie R.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Developing axons contain transcripts that are locally translated to influence the axonal proteome. Recent studies have shown that axonal transcripts include mRNAs encoding transcription factors. These mRNAs are translated to produce transcription factors that can be retrogradely trafficked back to the nucleus, where they regulate gene expression programs. These findings point to a novel mechanism of growth cone‐to‐nucleus signaling that occurs when growth cones encounter extracellular signaling molecules that stimulate local translation of these transcription factors, thereby influencing gene transcription. Here we summarize recent findings on local translation of transcription factors in axons and their roles in different neuronal processes such as neuronal specification, survival, and axon regeneration. Comprehensive axonal transcriptome studies have revealed transcripts that encode many more transcription factors and cofactors, suggesting a potentially broad role for this type of signaling. We review the progress on the approaches and tools that have been developed to study local translation and retrograde trafficking of transcription factors. We also highlight the challenges in the field and discuss the potential routes to resolving them. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 245–258, 2014